The right of the Ukrainian nation to self-determination (theoretical and legal aspects) - Волошина, Ю. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Research paper reveals an important aspect of the theory of national sovereignty, the rights of the Ukrainiannation to self-determination and security. Not all Ukrainians consider themselves as belonging to theUkrainian nation, and not the entire population of the Ukrainian state realizes that his very existence is a consequenceof self-determination of the Ukrainian nation. These questions reveal the means to respond to who we are – Ukrainians.